PANDANGAN ISLAM TENTANG DZIKIR DAN BUDDHA TENTANG MEDITASI - Kamaluddin Kamaluddin; Endang Ekowati; Dede Astica (Studia Sosia Religia, 2022)
This journal discusses the concept of dhikr in Islam and meditation in Buddhism. So that through this very long explanation there is a meeting point for a comparative analysis between dhikr and the views and differences in dhikr in Islam and views in Buddhism. So that at the end of the study can draw conclusions and find out other functions and analyzes of the concept of dhikr in Islam and thought in Buddhism.These two concepts aim to find a common ground towards the inner mind through different perspectives and different beliefs but towards the same understanding. In this journal the method that the author uses is a type of library research (library). This means that the author uses the theological method and comparative study because the author's study is related to worship which makes the concept of creation with God.